“I’m A Role Model”: Healthy Lifestyle of People Living with HIV in Special Region of Yogyakarta - Luluk Oktavia; Atik Triratnawati (Talenta Publisher, 2026)
Life expectancy of people living with HIV (PLHIV) has increased with advances in antiretroviral therapy, yet aging with HIV continues to bring medical, psychological, social, and cultural challenges. A healthy lifestyle is an important factor influencing quality of life. This study explores how PLHIV in Special Region of Yogyakarta perceive and practice a healthy lifestyle in their daily lives. Using a qualitative ethnographic approach, data were collected through in-depth interviews with five members of the Pita Merah Jogja (PMJ) community and documentation of their activities. Findings show that PLHIV in Special Region of Yogyakarta position themselves as role models who resist stigma and discrimination through healthy practices. These include physical activity, diet, sleep regulation, avoidance of smoking and alcohol, stress management, maintaining body weight, hydration, and supplement use. Each practice is shaped by life experiences, body condition, personal preferences, cultural values, and social support. Physical activity is performed flexibly; diet balances nutrition, culture, and enjoyment; sleep relates to immunity and emotional stability; and stress management is guided by Javanese values such as nrimo ing pandum. Hydration and supplement use reflect varying levels of medical discipline and daily habit. In conclusion, a healthy lifestyle among PLHIV in Yogyakarta is multidimensional, involving not only biomedical but also psychosocial and cultural aspects. These findings highlight the importance of health promotion strategies that integrate subjective experiences and local contexts to effectively improve the quality of life of PLHIV.